An Emerging Frontier in Intercellular Communication: Extracellular Vesicles in Regeneration - Avalos, Priscilla N.; Forsthoefel, David J. (Frontiers in Cell and Developmental Biology, 2022)
Regeneration requires cellular proliferation, differentiation, and other processes that are regulated by secreted cues originating from cells in the local environment. Recent studies suggest that signaling by extracellular vesicles (EVs), another mode of paracrine communication, may also play a significant role in coordinating cellular behaviors during regeneration. EVs are nanoparticles composed of a lipid bilayer enclosing proteins, nucleic acids, lipids, and other metabolites, and are secreted by most cell types. Upon EV uptake by target cells, EV cargo can influence diverse cellular behaviors during regeneration, including cell survival, immune responses, extracellular matrix remodeling, proliferation, migration, and differentiation. In this review, we briefly introduce the history of EV research and EV biogenesis. Then, we review current understanding of how EVs regulate cellular behaviors during regeneration derived from numerous studies of stem cell-derived EVs in mammalian injury models. Finally, we discuss the potential of other established and emerging research organisms to expand our mechanistic knowledge of basic EV biology, how injury modulates EV biogenesis, cellular sources of EVs in vivo, and the roles of EVs in organisms with greater regenerative capacity.